Compactness in spaces of inner regular measures and a general Portmanteau lemma - Volker Krätschmer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The new aspect is that neither assumptions on compactness of the inner approximating lattices nor nonsequential continuity properties for the measures will be imposed. As a providing step also a generalization of the classical Portmanteau lemma will be established. The obtained characterizations of compact subsets w.r.t. the weak topology encompass several known ones from literature. The investigations rely basically on the inner extension theory for measures which has been systemized recently by König ([8], [10],[12]).
Keywords: C65; 330; Inner premeasures; weak topology; generalized Portmanteau lemma